Folate binding protein: therapeutic natural nanotechnology for folic acid, methotrexate, and leucovorin. Issue 7 (3rd February 2017) - Merzel, Rachel L.; Boutom, Sarah M.; Chen, Junjie; Frey, Carolina; Shedden, Kerby; Marsh, E. Neil G.; Banaszak Holl, Mark M.
Abstract : Folate binding protein aggregates into nanoparticles, the volume of which are dependent on both the concentration and identity of the ligand. Variations in volume suggest differences in biological trafficking and therapeutic action. Abstract : Blood serum proteins play a critical role in the transport, biodistribution, and efficacy of systemically-delivered therapeutics. Here, we have investigated the concentration- and ligand-dependent aggregation of folate binding protein (FBP), focusing in particular on folic acid, an important vitamin and targeting agent; methotrexate, an antifolate drug used to treat cancer and rheumatoid arthritis; and leucovorin which is used to decrease methotrexate toxicity. We employed atomic force microscopy to characterize, on a particle-by-particle basis, the volumes of the FBP nanoparticles that form upon ligand binding. We measured the distribution of FBP nanoparticle volumes as a function of ligand concentration over physiologically- and therapeutically-relevant ranges. At physiologically-relevant concentrations, significant differences in particle volume distributions exist that we hypothesize are consistent with different trafficking mechanisms for folic acid and methotrexate. In addition, we hypothesize leucovorin is trafficked and delivered like folic acid at therapeutically-relevant concentrations. We propose that changes in dosing procedures could improve the delivery and therapeutic index for methotrexate and other folic acid-targeted drug conjugates and imaging agents. Specifically, we suggest pre-binding the drugs to FBP may provide a better formulation for drug delivery of methotrexate for both cancer and rheumatoid arthritis. This would be analogous to pre-binding paclitaxel to albumin, which is already used in the clinic.